2018
DOI: 10.1021/acsphotonics.8b01048
|View full text |Cite
|
Sign up to set email alerts
|

InGaAs-Based Well–Island Composite Quantum-Confined Structure with Superwide and Uniform Gain Distribution for Great Enhancement of Semiconductor Laser Performance

Abstract: In the development of semiconductor lasers, it has been a dream all along to simultaneously obtain extremely wide and uniform gain distribution, because such a gain configuration can greatly enhance semiconductor laser performance. Hence, it has also been a huge challenge to realize this dream so far. In this paper, we are reporting a special InGaAs-based well–island composite quantum-confined structure, with which the best results to date in achieving both superwide and very uniform gain and power distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…The injection energy is 112.4 mJ. Three peaks are observed in the measured PL spectrum, in which two extra peaks appear due to the emissions from the In 0.15 Ga 0.85 As and In 0.12 Ga 0.88 As regions . With the Gaussian simulation, it is found that the combination of three Gaussian spectra with peaks at 980, 970, and 930 nm is exactly identical to the experimental PL spectrum.…”
Section: Results and Analysismentioning
confidence: 56%
“…The injection energy is 112.4 mJ. Three peaks are observed in the measured PL spectrum, in which two extra peaks appear due to the emissions from the In 0.15 Ga 0.85 As and In 0.12 Ga 0.88 As regions . With the Gaussian simulation, it is found that the combination of three Gaussian spectra with peaks at 980, 970, and 930 nm is exactly identical to the experimental PL spectrum.…”
Section: Results and Analysismentioning
confidence: 56%
“…In [31], significant depolarization of the heavy-hole-related electroluminescence was observed and attributed to in-plane strain fields caused by modulations of In composition. In reference [27], a special InGaAs-based well-island composite quantum-confined structure was demonstrated, and both super-wide and very uniform gain and power distributions were obtained. The spectral flatness of the output power reached 0.1 dB, and the gain bandwidth was broadened to six-folds broader than FWHM (full width at half the maximum) of the standard gain spectrum from a classic InGaAs quantum well under the same carrier density.…”
Section: Number Of Qwd Layersmentioning
confidence: 99%
“…A number of research groups have investigated nanostructures that can be considered as intermediate cases between QWs and QDs. These structures were referred to as modulated quantum wells [16,17], as quantum wires [18][19][20][21][22][23][24], as 'Wires-on-Well' (WoW) [25,26], and as 'Well-Island' [27]. One approach is to use a dense array of small-sized QDs [21,28,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В последнее время большой интерес вызывают наноструктуры, обладающие свойствами, промежуточными между свойствами КЯ и КТ [11][12][13][14][15]. Они вносят сравнимый с КЯ вклад в фототок, и при их формировании, как и в случае КТ, происходит бездефектная релаксация упругих напряжений.…”
unclassified